2022
DOI: 10.1007/s00170-022-10213-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning on tool path optimisation and cooling lubricant in induction heating-assisted single point incremental sheet forming of Ti-6Al-4V sheets

Abstract: Induction heating-assisted single point incremental sheet forming was established for Ti-6Al-4V thin sheets at closed and above beta-transus temperature (980 °C). In order to eliminate geometric inaccuracy and adherence of lubricant on the surface caused by elevated temperature, a cooling lubricant system was designed for the forming tool to decrease the thermal expansion and friction. A radial basis function (RBF)-based tool path optimisation was developed to study the measured geometric accuracy, temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The study applied a self-mixed liquid MoS 2 to pass through the ball roller to reduce the thermo-expansion during the process. The findings show that liquid lubricant helps reduce the springback [67] and enhances the surface quality where the wear marks and abrasive lubricant adhesion have been significantly removed.…”
Section: Ball-roller Toolsmentioning
confidence: 94%
See 2 more Smart Citations
“…The study applied a self-mixed liquid MoS 2 to pass through the ball roller to reduce the thermo-expansion during the process. The findings show that liquid lubricant helps reduce the springback [67] and enhances the surface quality where the wear marks and abrasive lubricant adhesion have been significantly removed.…”
Section: Ball-roller Toolsmentioning
confidence: 94%
“…According to the study, the tool provided high-performance levels in the electric heating-assisted SPIF process for Ti-6Al-4 V at 500 °C. Similarly, another study by Li et al [67] investigated on the proposed water-cooling ball-roller design in an induction heating-assisted SPIF process for Ti-6Al-4 V at 950 to 1100 °C. Figure 16b illustrates that the difference in this design is the orientation of the lubricating balls between the ball roller and the tool wall.…”
Section: Ball-roller Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is presented in the Section 3, uniform thinning of the sheet metal along the perimeter of the drawpiece was observed. This assumption was also the subject of research by other authors examining the SPIF of titanium and its alloys [45][46][47]. Models of flow curves (Figure 7a) at temperatures between 183 and 340 °C were prepared by approximating the experimental curves using the approach proposed by Naranjo et al [35].…”
Section: Numerical Modelmentioning
confidence: 99%
“…It was shown that the two-stage forming technique could significantly reduce the geometrical deviation, thickness variation, and forming time. Li et al [34] investigated the tool path optimisation of induction heating-assisted SPIF using machine learning. Material formability and surface quality were improved following the optimisation of the tool path and using machine learning; however, noticeable oxidation and alpha layer of the sheet material at heating temperature ~1040 • C were reported, and they were eliminated at ~950 • C. Frikha et al [35] explored incremental forming of grade 2 α titanium for biomedical application (hip cup prostheses).…”
Section: Introductionmentioning
confidence: 99%